Supply chain risk management: Review, classification and future research directions - Piyush Singhal; Gopal Agarwal; Murali Lal Mittal (International Journal of Business Science & Applied Management (IJBSAM), 2011)
In order to be more efficient, firms have adopted strategies such as outsourcing, global partnerships and lean practices. Although such strategies have tremendous abilities to improve the efficiencies but simultaneously they make the firms vulnerable to market uncertainties, dependencies and disruptions. Moreover, natural calamities and manmade crises have also put negative impact on strategic, operational and tactical performance of supply chains. These factors have triggered the interest of academia and industry to consider the risk issues as prime concerns. To capture the more fine-grained elements of diversified risk issues related to the supply chain we employ a multi-layered top town taxonomy to classify and codify the literature and put forward the probable dimensions for future research. We further study the pool of SCRM literature focusing on coordination, decision making and sector-wise SCRM implementation issues and derive relevant propositions.
Keywords: 650; supply chain risk management; risk; uncertainty; literature review